(untitled) (Editora Impacto Científico, 2025)
Diabetes Mellitus, as a chronic condition with increasing incidence among adolescents, presents a high risk for complications that negatively impact quality of life, justifying the importance of investigating this condition within the scope of Primary Health Care. Therefore, the objective of this study was to analyze the prevalence of DM complications in adolescents followed by the Family Health Strategy in a municipality in the Macro-West Region of Minas Gerais. To this end, a descriptive cross-sectional study was conducted, developed from secondary data obtained from the Citizen’s Electronic Health Record, between February and March 2024. Adolescents diagnosed with type 1 or type 2 DM were included, whose sociodemographic and clinical information was analyzed using descriptive statistics and the Chi-square test, adopting a significance level of p<0.05. Thus, it is observed that, among 64 adolescents evaluated, the prevalence of complications was 7.8%, predominating in males, aged between 15 and 19 years, with a BMI above the 85th percentile and use of combined drug treatment. Although no variable showed a statistically significant association with complications, important trends were identified, especially related to gender, treatment, and nutritional status. These findings allow us to conclude that, even with the low prevalence and the absence of a significant association, there are profiles that require greater clinical vigilance. The importance of Primary Care in early detection, continuous monitoring, and the implementation of health education strategies that promote self-care and prevent adverse outcomes in adolescence is reinforced. DOI: https://doi.org/10.56238/edimpacto2025.090-060